Experiences of women relocated due to the february 2023 earthquake in Turkey: a qualitative study - Esra Özer; Yeşim Çetinkaya Şen; Döndü Sevimli Güler; Gülten Güvenç (BMC Women's Health)
Abstract Background Women are disproportionately affected by disasters due to their vulnerability and limited access to resources. The purpose of this study is to investigate the health concerns and experiences of women who relocated to a different city following the February 2023 earthquake in Turkey. Methods Data was collected using a constructivist qualitative research design. Between May 1 and July 1 2023, interviews were conducted with female participants who relocated to a different city after the February 2023 earthquake in Turkey. The collected data underwent qualitative content analysis, adhering to the Standards for Qualitative Research Reporting (SRQR). The study utilized Graneheim and Lundman’s content analysis method to analyze the interview data. Interviews were transcribed. The transcripts were analyzed in the qualitative research software package ATLAS.ti 9. Results In the study, 32 women aged 19–43 years were interviewed. The results revealed four distinct categories and 10 sub-categories derived from the interviewees’ narratives. These four categories were physiological needs, safety concerns, need for love and belonging, and self-realization. Conclusions It was concluded that individuals who experience disasters face multiple hardships, especially related to these categories. Therefore, it is crucial to focus on the issues and requirements of survivors, particularly women belonging to vulnerable groups. One should not overlook the fundamental needs of women in service delivery.